Estereótipos do profissional da Contabilidade na percepção de estudantes de cursos preparatórios para ingresso no ensino superior - Luiz Ernani de Carvalho Junior (2015)
The present study aimed to find evidence that permits identification and categorization of the stereotype of the accounting professional from the students perspective in preparatory programs for entry into institutions of higher education (IHE). The theoretical platform was mainly guided by the theory of stereotypes. According to Lippmann (1922); Sá (1998); Deschamps and Moliner (2009); and Moscovici (2012), stereotyping is considered a psychosocial process that impacts individuals in their decisions, actions and cognitive capacities in environments where they act, in the case of Accounting and its professional, in educational systems and in the business world. Stereotyping influences students career choices and is also used by them to support their choices (DECOSTER, 1971; STEELE; ARONSON, 1995; SCHMADER; JOHNS, 2003; and BYRNE; WILLIS, 2005). The data collection methodology adopted was the structured interview. The database analyzed comprised 241 respondents, including students from preparatory programs for entry into IHE. Of the respondents analyzed, 151 (62.66%) are female and 90 (37.34%) are male. Only 11.98% of the respondents claimed to know accounting and its professionals well. Seventy per cent (70%) of the 241 respondents erroneously indicated Accounting Science to be an Exact Science. Concerning both the program and the career choices of the respondents, a low level of attractiveness of the Accounting Science program was detected. Only 4 respondents indicated the program as an option for entry into IHE. 201 (83.40%) of them claimed no or little chance of choosing Accounting Science. It was found that accounting professionals are stereotyped positively for all characteristics: creativity, dedication to studies, teamwork, communication, leadership, risk propensity and ethics by the respondent public, suggesting more positive perceptions of the current survey respondents compared to previous surveys. The gender stereotype of the profession found in the present study was masculine. From the analysis of the manner in which the respondents perceive the way the professionals are seen by the business world, they are considered to be important for the enterprises and the accountants try to meet the market needs as updated, modern and dynamic professionals. They were not considered well paid professionals when compared to other professions, nor were they well considered by the market. In the latter case, men have a more negative perception than women. The interview impacted the perceptions of the interviewees in a subtle but positive way. It was concluded that the respondents positively stereotyped the professionals for the characteristics mentioned above, although the results suggest that they are not very creative or willing to take risks. The level of attractiveness for the program was low. In the professional sphere, it was observed that the professionals are perceived as important for the institutions and try to be updated, modern and dynamic even though they are not well valued, nor well compensated. These results suggest a scenery in which Accounting, its professionals and the program face a great challenge to revert the stereotypes with the researched public, highlighting the positive perceptions about its professionals.